Development Of Entrepreneurship Through Effective Tax Burden Management - Turaev Shavkat Shukhratovich; Berdiboev Oltinboy Abdiboqi ugli; Abdiev Nasir Rakhimovich (Genius Journals, 2026)
This article analyzes the current tax policy in the Republic of Uzbekistan and substantiates the need for its improvement. The article highlights the main directions aimed at increasing the efficiency of the tax system, creating a favorable environment for business entities, and stabilizing budget revenues. Also, the experience of foreign countries in reforming tax policy was studied, and recommendations that can be applied in the conditions of Uzbekistan were put forward.
Keywords: tax policy; tax reform